2018
DOI: 10.1109/jssc.2018.2821139
|View full text |Cite
|
Sign up to set email alerts
|

An FDD Wireless Diversity Receiver With Transmitter Leakage Cancellation in Transmit and Receive Bands

Abstract: Antenna-coupling group delay limits the cancellation bandwidth of conventional self-interference cancellers (SICs), making it difficult to ensure isolation in both transmit (TX) and receive (RX) bands. Isolation over both bands is achieved in the dual-path receiver architecture proposed in this paper. The main path consists of a highly linear current-mode RX with a passive RF SIC. The auxiliary path implements a notch in the TX band followed by an adaptive digital equalizer whose output is used to suppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Transmit noise can be considered as the noise input to the transmit system (generated by spectrometer) multiplied by the transmit gain and the additional contributions of other noise generating elements (amplifiers and the cancellation circuit) as summarized in Equation (). With proposed cancellation hardware, it is shown that it is possible to isolate the transmit noise in addition to the leak signal for a given transmit gain, consistent with the works by Montanari et al, 25 Zhou et al, 26 and Emara et al 25 …”
Section: Discussionsupporting
confidence: 84%
“…Transmit noise can be considered as the noise input to the transmit system (generated by spectrometer) multiplied by the transmit gain and the additional contributions of other noise generating elements (amplifiers and the cancellation circuit) as summarized in Equation (). With proposed cancellation hardware, it is shown that it is possible to isolate the transmit noise in addition to the leak signal for a given transmit gain, consistent with the works by Montanari et al, 25 Zhou et al, 26 and Emara et al 25 …”
Section: Discussionsupporting
confidence: 84%
“…The transfer function decreases as the LO frequency goes up, corresponding to decreased STLO. Although the transconductance flicker noise transferred to output is decreased with decreased STLO, the accompanied conversion gain also degrades as disclosed in (1) and (3). Moreover, as in the previous analysis, the transconductance flicker noise is also modulated by the random offset voltage Vos3 applied to the gate of switches.…”
Section: Theory Verification By Simulationsmentioning
confidence: 64%
“…Specifically, for tentative specifications of thermal noise figure, NF=10 dB, and conversion gain CG=13 dB, the parameter requirements for gm0=11 mS and RL=800 Ω is computed by (1) and (18) with typical S as in Table 1. And it is also verified that t1 =27 ps.…”
Section: Theory Verification By Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…H. Khatri et al,(2010) and A. Cicalini et al,(2006) proposed TX leakage filtering active cancellation techniques [9][10][11]. Lederer and Huemer (2011), Frotzscher and Fettweis (2008), and Kahrizi et al,(2008) discussed interference cancellation algorithms using adaptive based LMS and measured error to suppress noise through stopband of the frequency flat duplex [12][13].…”
Section: Introductionmentioning
confidence: 99%